Beliefs about medicines and adherence in women with breast cancer on adjuvant endocrine therapy. (April 2022) - Tan, Eng Hooi; Wong, Andrea Li Ann; Tan, Chuan Chien; Wong, Patrick; Tan, Sing Huang; Ang, Li En Yvonne; Lim, Siew Eng; Chong, Wan Qin; Ho, Jingshan; Lee, Soo Chin; Tai, Bee Choo
The Beliefs about Medicines Questionnaire (BMQ) and Adherence Starts with Knowledge (ASK-12) questionnaire were originally developed and validated in Western populations to assess beliefs and barriers to medication adherence. The study aim is to validate the BMQ and ASK-12 questionnaire for use in a Singapore population with early stage breast cancer. English-speaking women on adjuvant endocrine therapy ( n  = 157) were recruited. The BMQ-Specific showed good internal consistency with structural validity. The internal consistency of BMQ-General and ASK-12 Behaviour scale improved with the new factor structure obtained from exploratory factor analysis. Further studies are needed to confirm these factor structures.